Biochar addition to compost heat recovery systems improves heat conversion yields - Pivato, Alberto; Malesani, Rachele; Bocchi, Stefano; Rafieenia, Razieh; Schievano, Andrea (Frontiers in Energy Research, 2024)
Introduction: Compost heat recovery systems (CHRS) represent an emerging technology to recover residual woody biomass from agroforestry and forestry activities and use the heat that is naturally produced during aerobic biodegradation (composting). However, a low oxygen concentration in the gas phase and self-drying and compaction of the compost body often limit efficient oxidation by microbial communities. Woodchip-derived biochar has often been proposed as a bulking agent and improver of water retention and of oxygen accessibility in the composting process, but the literature reporting its effects in the CHRS is scarce. Methods: Here, biochar (average particle size of 10 mm) was added at 10% (on weight basis) to chipped pruning residues into two bench-scale-controlled reactors (0.2 m3), operated in parallel for 57 days. Results and Discussion: The addition of 10% (w/w) biochar to the composting body increased biodegradation yields by approximately 50% and improved oxidation rates over readily biodegradable organic fractions (addition of cheese whey). Temperatures were on average 1.34°C higher, and heat extraction flux was also improved in the presence of biochar (0.3 kW/m3) versus in its absence (0.1 kW/m3). The organic matter mass balance resulted in approximately 50% higher biodegradation yield and improved oxidation rates over readily biodegradable organic fractions. Microbial analysis highlighted a higher concentration of thermophilic species and a lower concentration of well-known pathogenic and antibiotic-resistant genera in the presence of biochar.